Competition between managed honeybees and wild bumblebees depends on landscape context - Herbertsson, Lina; Lindström, Sandra A.M.; Rundlöf, Maj; Bommarco, Riccardo; Smith, Henrik G. (Basic and applied ecology, 2016)
Honeybees might outcompete wild bees by depleting common resources, possibly more so in simplified landscapes where flower-rich habitats have been lost. We tested this by experimentally adding honeybee hives to nine sites while ensuring that ten additional sites were free from hives. The landscape surrounding each geographically separated site either held low (homogeneous landscape) or high (heterogeneous landscape) proportions of semi-natural grassland. Adding honeybees suppressed bumblebee densities in field borders and road verges in homogeneous landscapes whereas no such effect was detected in heterogeneous landscapes. The proportional abundance of bumblebee species with small foraging ranges was lower at honeybee sites than at control sites in heterogeneous landscapes, whereas bumblebee communities in homogeneous landscapes were dominated by a single species with long foraging range irrespective of if honeybees were added or not. We conclude that honeybees can impact bumblebee densities, but that landscape heterogeneity modified this effect. Honigbienen können Wildbienen durch Konkurrenz verdrängen, indem sie häufige Ressourcen erschöpfen, was möglicherweise häufiger in einfach strukturierten Landschaften geschieht, in denen blütenreiche Habitate verloren gegangen sind. Wir testeten dies, indem wir experimentell Bienenstöcke an neun Standorten hinzufügten und in zehn weiteren sicherstellten, dass keine Bienenstöcke vorhanden waren. Die Landschaften, die die geographisch voneinander getrennten Standorte umgaben, enthielten entweder einen geringen (homogene Landschaft) oder einen hohen (heterogene Landschaft) Anteil von naturnahem Grasland. In homogenen Landschaften reduzierte die Hinzugabe von Honigbienen die Hummeldichten in Feldrainen und im Straßenbegleitgrün, während in heterogenen Landschaften kein derartiger Effekt beobachtet werden konnte. In heterogenen Landschaften war der proportionale Anteil von Hummelarten mit kleinem Sammelaktionsgebiet an Honigbienenstandorten geringer als an Kontrollstandorten. In homogenen Landschaften wurden die Hummelgemeinschaften dagegen von einer Art mit großem Sammelaktionsgebiet dominiert, unabhängig davon, ob Honigbienen hinzugefügt worden waren oder nicht. Wir schließen, dass Honigbienen Hummeldichten beeinflussen können, dass aber dieser Effekt durch die Heterogenität der Landschaft modifiziert wird.